The effect of educational intervention on the quality of life of women suffering from pregnancy-related nausea and vomiting: a systematic review - Piri, Mahsa; Maleki, Azam; Saed, Omid (The journal of maternal-fetal & neonatal medicine, 2024)
The present study aimed to determine the influence of educational interventions on improving the quality of life (QOL) of women suffering from pregnancy-related nausea and vomiting (NVP) as a systematic review. The current systematic review followed the standard Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist guideline. The English electronic databases were used to identify relevant studies published 2000 until 14 August 2023. The search strategies employed were based on Mesh browser keywords and free-text words. The study risk of bias was evaluated using the Cochrane Collaboration's tool for assessing the risk of bias tools and publication bias was evaluated using a funnel plot and Begg and Egger tests. The heterogeneity of the studies was evaluated using and tau-squared tests. Data were analyzed using the RevMan 5 software. Results of the random-effects meta-analysis were presented using the standard mean difference, along with a 95% confidence interval (CI). Out of the seven randomized clinical/control trial (RCT) studies with a total of 946 subjects included in the review, five studies reported a significant result, indicating that the interventions had a statistically significant effect on the QOL of women suffering NVP and in two studies did not have a significant result. A subgroup analysis was done based on the type of quality-of-life measurements. The pooled standardized mean difference (SMD) of four articles (Nausea and Vomiting Pregnancy Quality of Life, NVPQOL) with a total of 335 subjects was -2.91, and CI of -4.72 to -1.11, value = .002, = 97.2%. The pooled SMD of three articles (SF36) with a total of 611 subjects was -0.05, and CI of -0.23 to -0.12, value = .550, = 10%. The overall results of the analysis indicated that educational intervention had a small positive impact on the QOL of women experiencing NVP. However, to draw a better conclusion, it is recommended to conduct further studies with larger sample sizes and longer follow-up periods.